2008
DOI: 10.1007/s10800-008-9738-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical, SEM and XPS investigations on phosphoric acid treated surgical grade type 316L SS for biomedical applications

Abstract: A simple surface pre-treatment method was attempted to establish a stable passive layer on the surface of surgical grade stainless steel (SS) of type 316L for biomedical applications. Surgical grade type 316L SS specimens were subjected to H 3 PO 4 treatment for 1 h by completely immersing them in the acid solutions to develop a passive barrier film. The effect of various concentrations of phosphoric acid on the localized corrosion resistance behavior of type 316L SS was investigated through electrochemical te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Some authors suggested that phosphorous could be incorporated within the passive film [13,65] and/or could precipitate as iron and/or chromium phosphates [11,22,29]. A high phosphate content was observed by XPS (see Table 5) on all samples, as shown in Fig.…”
Section: Surface Analyses: Xps and -Ramanmentioning
confidence: 73%
See 1 more Smart Citation
“…Some authors suggested that phosphorous could be incorporated within the passive film [13,65] and/or could precipitate as iron and/or chromium phosphates [11,22,29]. A high phosphate content was observed by XPS (see Table 5) on all samples, as shown in Fig.…”
Section: Surface Analyses: Xps and -Ramanmentioning
confidence: 73%
“…To the best of our knowledge, all these studies have been performed in pure phosphoric acid [12][13][14] or polluted phosphoric acid, i.e.pure phosphoric acid with the addition of chloride and sulfate ions at various temperatures [3,[14][15][16][17][18][19][20][21][22][23][24]. Sanchez-Tovar et al [14,17] have shown that between 20 • C and 60 • C, the temperature had no effect on corrosion potential, passive current and passive range on AISI 316L SS in pure phosphoric acid (40 wt%).…”
Section: Introductionmentioning
confidence: 99%
“…2,5,18,[30][31][32] For example, Lewis et al 2 reported that the increase in the phosphoric acid concentration results in increasing in both the passive layer thickness and the chromium and ferrous phosphate contents.…”
Section: Xps Analysis Of Passive Layers Fe-18cr-12mn-nmentioning
confidence: 99%
“…The largest part of stainless steel equipment failure are caused by chloride ions, particularly in cooling water systems the pitting and crevice corrosion are still the serious problems of stainless steel 3 . Surface treatment procedures such as electro polishing, low temperature nitridization and passivation have been used to enhance the resistivity of the metals [4][5][6][7] .The increasing application of the RESEARCH ARTICLE stainless steel to improve efficient and environmentally complicated method, corrosion and either inhibitors or conducting polymer coating [8][9][10][11][12] . In recent times, conducting polymers have received considerable attention as corrosion protective coatings for oxidizable metals.…”
Section: Introductionmentioning
confidence: 99%